Familial hypercholanemia Type 1 with associated glucose 6 phosphate dehydrogenase deficiency presenting with acute liver failure in the immediate newborn period - Jini, Pepu; Tani, Tilling (Indian Journal of Case Reports, 2026)
Familial hypercholanemia, a very rare genetic disorder, is caused by defective bile acid transport. It can present with features of cholestasis, such as jaundice, pruritus, fat malabsorption, and fat-soluble vitamin deficiencies in early childhood. We report a case of familial hypercholanemia Type 1 presenting as acute liver failure in the immediate newborn period, from 0 h of life. This rare disorder was also incidentally found in association with G6PD deficiency, although there were no features of hemolysis in the infant. With this report, we hereby highlight the existence of this very rare genetic disorder in this part of India and that this disorder is an important differential diagnosis for acute liver failure in the immediate newborn period. Use of Ursodeoxycholic acid provided an excellent outcome in the baby till the follow-up period of 1 year.